2016
DOI: 10.1007/s00018-016-2255-5
|View full text |Cite
|
Sign up to set email alerts
|

The recognition of ubiquitinated proteins by the proteasome

Abstract: The ability of ubiquitin to form up to eight different polyubiquitin chain linkages generates complexity within the ubiquitin proteasome system, and accounts for the diverse roles of ubiquitination within the cell. Understanding how each type of ubiquitin linkage is correctly interpreted by ubiquitin binding proteins provides important insights into the link between chain recognition and cellular fate. A major function of ubiquitination is to signal degradation of intracellular proteins by the 26S proteasome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
219
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(222 citation statements)
references
References 75 publications
(122 reference statements)
2
219
0
1
Order By: Relevance
“…Because K48-ubiquitination directs proteins to the proteasome (Grice and Nathan, 2016), we hypothesized that Smurf1, but not Parkin, might function in recruitment of the proteasome to Mtb-associated structures. Indeed, there was a significant reduction in colocalization of the proteasomal 20S β2i subunit with Mtb-associated structures in Smurf1 −/− BMDMs compared to wild-type BMDMs (Figure 5F and 5G).…”
Section: Resultsmentioning
confidence: 99%
“…Because K48-ubiquitination directs proteins to the proteasome (Grice and Nathan, 2016), we hypothesized that Smurf1, but not Parkin, might function in recruitment of the proteasome to Mtb-associated structures. Indeed, there was a significant reduction in colocalization of the proteasomal 20S β2i subunit with Mtb-associated structures in Smurf1 −/− BMDMs compared to wild-type BMDMs (Figure 5F and 5G).…”
Section: Resultsmentioning
confidence: 99%
“…Polyubiquitination events with K 48 and K 29 linkages are known to mark target proteins for degradation by the 26S proteasome (Chau et al ., ; Johnson et al ., ). K 63 plays a role in intracellular signalling and DNA repair (Deng et al ., ; Sobhian et al ., ; Bennett & Harper, ; Grice & Nathan, ). The observation of protein ubiquitination in phloem samples over time showed that especially proteins larger than 75 kDa lost their ubiquitin modification, while the pattern of smaller proteins remained nearly unchanged (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, proteasomes are able to distinguish between these two modes of polyubiquitin linkage. 87 In our K48-linked trimer models, the hydrophobic patch is packaged around the I44 residue of the central and proximal monomers (Figure 8), and the alternative hydrophobic binding site of the I36 patch is exposed. 88 The opposite scenario is true in one state of our K11-linked model, and the fully compact state of K11 trimers buries all three I36 patch residues while simultaneously exposing all three I44 patch residues.…”
Section: Discussionmentioning
confidence: 99%